Effects of nitrogen and potassium combination treatments on growth, nutrient economy, yield potential and zerumbone content of Zingiber zerumbet (L.) Smith / Siti Nurul Atikah Abu Samah - Abu Samah, Siti Nurul Atikah (2020)
Zingiber zerumbet (L.) Smith or also is known as pine cone ginger has been extensively studied because of its tremendous medicinal benefits. However, little knowledge is available on the cultivation science of this species grown under humid tropical environment which lead to varying rhizome and zerumbone yield depending on practices. Growth and Yield are generally limited by fertilization formulation and amount in particular nitrogen (N) and potassium (K). The objective of this study was to quantify the overall growth, biomass production, phenological development, nutrient uptake and rhizome yield expressed as fresh weight or zerumbone content as affected by N and K fertilization levels. A field study was carried out at the Botanical Garden Shah Alam, Selangor, Malaysia from February 2016 to January 2017. The experiments were designed as a factorial experiment consisting of two N levels and four K levels, with a total of eight treatment combinations. The N levels were normal – 60 and high – 120 kg N ha-1 and the K levels were 0, 60, 120 and 180 kg ha-1 for each N level, while phosphorus (P) level was kept constant at 70 kg ha-1. A total of 1120 plants were planted in Randomized Complete Block Design (RCBD) with four replications. The sampling plants consisted of 256 plants with the rest of the other plants (864) were used as guard rows. Seven principal growth stages namely bud and leaf development, formation of stem or tillering, peduncle elongation, inflorescence emergence, flowering and inflorescence senescence were distinctively defined. A growing degree day (GDD) of 373 - 390°C-d and 474 - 510°C-d were required for the formation of the first leaf and tiller while a GDD of 2246 - 2332°C-d for flower blooming. In general, the results showed that both N and K were important for the overall growth, however, their effects differed with growth parameters and stages. The high K rates (120 and 180 kg ha-1) had significantly increased the plant height, primary root number, leaf dry mass (LfDM), stem dry mass (StDM), total root dry mass (TotRtDM), primary root dry mass (PriRtDM), leaf area (LA), leaf mass ratio (LfMR), stem mass ratio (StMR), total root mass ratio (TotRtMR), rhizome mass ratio (RhMR), root to shoot ratio (R/S), leaf area ratio (LAR) and specific leaf area (SLA) at mainly active tillering stage (186 DAT). The high K rates also significantly increased the new rhizome P, leaf and stem K concentrations and leaf and stem K content at mainly maturity stage (290 days after transplanting (DAT)). Conversely, the K effect was significant in zerumbone content across harvest and total zerumbone yield at the rhizome expansion stage (237 DAT) under zero K rate (0 kg ha-1). The amount of nutrient taken up was the highest in N followed by K and P for both rhizome expansion and maturity stages. In general, as the N and K level increased, the biomass production, partitioning and nutrient concentrations and contents and zerumbone content were increasing. These results are important for better cultivation practices of Z. zerumbet.